Strategi Kepemimpinan Kepala KUA dalam Meningkatkan Motivasi Kerja Pegawai di Kantor Urusan Agama (KUA) Kecamatan Siliragung Kabupaten Banyuwangi - Siti Rosiatun Ulfa; Kun Wazis (Maddah: Journal of Advanced Da'wah Management Research, 2022)
Motivation is important thing to be considered leader. If they want every employee be able make positive contribution to achievement of an institution, because with motivation, employee will have high enthusiasm in carrying out the tasks assigned to him. If he does not have motivation to work, the results will not be effective and also satisfying. focus of problems :1)What is Leadership Strategy of Head KUA in Improving Employee Work Motivation in the Office of Religious Affairs (KUA) of Siliragung District?.2)How is strategy of the Head KUA in overcoming the Supporting and Inhibiting Factors in Increasing Employee Work Motivation in Office of Religious Affairs (KUA) Siliragung District? The aims of this study were:1)To determine leadership strategy of Head KUA in Improving Work Motivation of Employees at the Office of Religious Affairs (KUA) Siliragung District.2)To find out the strategy the Supporting Factors and Inhibiting Factors of Head KUA in Improving Employee Work Motivation at the Office of Religious Affairs (KUA) Siliragung District.The type of research used is field research, which can also be referred to as method for collecting qualitative data. This study uses descriptive taxonomy, The data used in-depth interviews, participatory observation,and documentation.The results this study include: 1)The strategy of the head KUA in increasing employee motivation in KUA Siliragung District is recognizing personal well, recognizing employee performance, being open to employees, and providing sense of security. 2)strategy of the head KUA in overcoming the supporting and inhibiting factors is providing assistance always providing motivation and approach to personal employees.